Strategi Pemasaran Multi Level Syariah PT. Ahadnet Indonesia dan Multi Level Konvensional PT. DXN Indonesia Cabang Makassar - K, Amiruddin (Universitas Islam Negeri Alauddin Makassar, 2021)
This research aims to find out how the concept of Sharia marketing vs conventional marketing and aims to know the product marketing strategy in PT. Ahad Net and PT. DXN Makassar Branch, and know the differences and similarities of the two multilevels. The type of research used is a type of qualitative research. The results of the research analysis then the author found that the concept of spiritual-based sharia marketing management (velue) that began with the sincere intention and pleasure of Allah to obtain double-dimensional benefits namely matril and siprituil (falah). While conventional marketing management prioritizes speculation and exploitation to achieve the greatest material profit. Sunday net marketing strategy prioritizes morality as the main capital for a marketing to be trusted and trusted by consumers, then the products marketed are products that are guaranteed quality and guaranteed halal again good, while dxn product marketing strategy DXN As a multi-level conventional marketing prioritizes the superiority of its products and incentives are high enough and loaded with speculation in achieving its goal of maximum material benefits.